Condition of larval (furcilia VI) and one year old juvenile Euphausia superba during the winter–spring transition in East Antarctica. (September 2016) - Virtue, Patti; Meyer, Bettina; Freier, Ulrich; Nichols, Peter D.; Jia, Zhongnan; King, Rob; Virtue, Jacob; Swadling, Kerrie M.; Meiners, Klaus M.; Kawaguchi, So
Abstract: Antarctic krill, Euphausia superba, is an important species in the Southern Ocean ecosystem. Information on krill condition during winter and early spring is slowly evolving with our enhanced ability to sample at this time of year. However, because of the limited spatial and temporal data, our understanding of fundamental biological parameters for krill during winter is limited. Our study assessed the condition of larval (furcilia VI) and one year old juvenile krill collected in East Antarctica (115°E–130°E and 64°S–66°S) from September to October 2012. Krill condition was assessed using morphometric, elemental and biochemical body composition, growth rates, oxygen uptake and lipid content and composition. Diet was assessed using fatty acid biomarkers analysed in the krill. The growth rate of larvae was 0.0038 mm day with an inter-moult period of 14 days. The average oxygen uptake of juvenile krill was 0.30±0.02 μl oxygen consumed per mg dry weight per hour. Although protein was not significantly different amongst the krill analysed, the lipid content of krill was highly variable ranging from 9% to 27% dry weight in juveniles and from 4% to 13% dry weight in larvae. Specific algal biomarkers, fatty acids ratios, levels of both long-chain (≥C20 ) monounsaturated fatty acids and bacterial fatty acids found in krill were indicative of the mixed nature of dietary sources and the opportunistic feeding capability of larval and juvenile krill at the end of winter.